Alternatif model pemanfaatan berkelanjutan tinggalan budaya bawah air di Indonesia - Alqiz Lukman; Panji Syofiadisna; Shinatria Adhityatama; nfn. Harriyadi; Dewangga Eka Mahardian; Erni Trisnawati (Berkala Arkeologi, 2021)
Indonesia’s abundant underwater cultural heritage is potential resource for the pride of national identity, as well as the socio-economic growth. However, current utilization of such resource is still merely limited to exploitable commodities with no consideration to its sustainability. This article aims to identify problems in the regulatory aspect of the utilization of underwater cultural heritage in Indonesia and to propose an alternative utilization model to respond the identified problems. Data collection for this study includes structured interview and literature study. Interviewees are selected people from The Ministry of Education, Culture, Research, and Technology, The Ministry of Marine Affairs and Fisheries, and Association of Indonesian Archaeologist.  The results of qualitative analysis on the interview show overlapping implementation of four regulations regarding underwater cultural heritage. This article proposes a utilization concept adopted from the ecosystem restoration concession model as an alternative for sustainable utilization of underwater cultural heritage. Keywords: Underwater cultural heritage; heritage management; BMKT; Underwater archaeology; shipwreck.